Unravelling the pH-dependence of a molecular photocatalytic system for hydrogen production1. Issue 8 (14th August 2015) - Reynal, Anna; Pastor, Ernest; Gross, Manuela A.; Selim, Shababa; Reisner, Erwin; Durrant, James R.
<x xml:space="preserve">Abstract</x> The electron-donating ability of the sacrificial agent and the protonation of the catalyst determine the optimum pH for hydrogen production.